2021
DOI: 10.1128/aac.02263-20
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer-Agar-Based Direct Phenotypic Drug Susceptibility Testing on Sputum in Eswatini Rapidly Detects Mycobacterium tuberculosis Growth and Rifampicin Resistance Otherwise Missed by WHO-Endorsed Diagnostic Tests

Abstract: BACKGROUND: Xpert®MTB/RIF rapidly detects resistance to rifampicin (RR), however this test misses the I491F-RR conferring rpoB mutation, common in Southern Africa. In addition, Xpert®MTB/RIF does not distinguish between viable and dead Mycobacterium tuberculosis (MTB). OBJECTIVE: To investigate the ability of thin layer agar (TLA) direct drug-susceptibility testing (DST) to detect MTB and its drug-resistance profiles in field conditions in Eswatini. DESIGN: Consecutive samples were tested in parallel with Xper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, we showed a high positivity frequency, which may be due to selection bias, and the inclusion criteria were highly suspected cases of tuberculosis. Delay in testing of the specimens affects the positive results and increases the chance of contamination; thus, thin-layer agar is a suitable method for peripheral laboratories (21). Studies conducted in Switzerland showed a high positivity rate in the detection of M. tuberculosis using thin-layer agar in low-resource settings (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed a high positivity frequency, which may be due to selection bias, and the inclusion criteria were highly suspected cases of tuberculosis. Delay in testing of the specimens affects the positive results and increases the chance of contamination; thus, thin-layer agar is a suitable method for peripheral laboratories (21). Studies conducted in Switzerland showed a high positivity rate in the detection of M. tuberculosis using thin-layer agar in low-resource settings (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Delay in testing of the specimens affects the positive results and increases the chance of contamination; thus, thin-layer agar is a suitable method for peripheral laboratories (21). Studies conducted in Switzerland showed a high positivity rate in the detection of M. tuberculosis using thin-layer agar in low-resource settings (21,22). More M. tuberculosis -positive cultures were detected using thin-layer agar and MGIT than with Lowenstein Jensen culture method.…”
Section: Discussionmentioning
confidence: 99%
“…This is critical as although phenotypic DST is considered by many a step backwards to improve DR-TB testing, there is evidence that show that INH-and RIF resistant TB cases are missed when using genotypic DST, resulting in misleading treatments (23). This is mainly due to the fact that genotypic DST can miss the detection of novel resistance-conferring mutations that are otherwise detected by phenotypic DST (24)(25)(26)(27)(28)(29).…”
Section: Phenotypic Dstmentioning
confidence: 99%
“…By the time of the next drug resistance survey in 2017, 56% of rifampicin resistance was conferred by the I491F mutation (World Health Organization, 2020). The Eswatini National Tuberculosis Control Programme has since proposed presumptively treating all isoniazid-resistant TB as MDR-TB until phenotypic testing has been completed, as most I491F mutations are present in isoniazid resistant strains (Ardizzoni et al, 2021).…”
Section: Implications For Diagnosticsmentioning
confidence: 99%